Crablet of Mud Crab Scylla Olivacea Production from the Different Stages of Larvae fed Artemia Nauplii Enriched Using Nannochloropsis sp - Gunarto Gunarto; Andi Parenrengi; Early Septiningsih (Hasanuddin University, 2016)
Improvement of feed quality for mangrove crab larvae rearing is one of theimportant factors to increase of crablet production. The aim of the research was to knowthe influenzing of enriched Artemia nauplii using Nannochloropsis sp fed to the differentstages of larvae Scylla olivacea on crablet production. Twelve units of tanks volume 250L filled with saline water salinity 30 ppt, aerated, then stocked with new hatched mud crablarvae zoea-1 at the density 100 ind./L. The larvae zoea-1 were fed rotifer, Brachionus sp.and after zoea-3, beside fed by rotifer, the larvae were also fed by Artemia naupli. Fourtreatments were tested, namely: A). Artemia nauplii enriched using Nannochloropsis sp.was given to the larvae zoea-3 until develop to megalop stage. B). Artemia nauplii enrichedusing Nannochloropsis sp was given to the larvae zoea-4 until develop to megalop stage.C). Artemia nauplii enriched using Nannochloropsis sp was given to the larvae zoea-5 stageuntil develop to megalop stage. D). Artemia nauplii without enriched using Nannochloropsissp. was given to the larvae zoea-3 until develop to megalop stage. Result of the researchshowed that the highest of Larvae Development Indexes and Megalop Occurence Indexeswas obtained in treatment A and resulted the highest of crablet production, then followed bytreatment C and B and those were significantly different (P<0.05) with the crablet productionin treatment D. The use of Artemia nauplii enriched by Nannochloropsis sp. to feed larvae,S. olivacea stage zoea-3 to zoea-5 until develop to the megalop stage is one of the key factorto enhance the crablet production. By this finding, the crablet production in hatchery will beincreased and the mud crab culture in brackishwater pond able to developed.